Implementing Task Based Approach in ESP Education: Business schools as a Case Study - EL ARBAOUI, Fatima Zahra (LPPM Universitas Advent Indonesia, 2024)
It is asserted that task-based instruction improves the environment and makes it easier to teach English. Due to this, many EF language teachers and syllabus developers have recently turned their attention to task-based language education. With a focus on Business English instruction in Moroccan universities, this study examined ESP (English for Specific Purposes) teaching within the paradigm of task-based language teaching. To that purpose, information from a total of 234 students and 21 teachers was gathered using questionnaires. First, questionnaires were created to gather learners’ opinions on the impact of the given assignments on their language development, learning processes, and skill acquisition. This study also tried to investigate how instructors felt about using a task-based approach in ESP classes. The findings indicate that both students and instructors have positive opinions and attitudes concerning (TBLT). They believed that the inclusion of this method, specifically ESP, in language instruction creates favourable teaching and learning conditions because it engages students in tasks that are pertinent to their academic and professional needs. As a result, it is advised to use a task-based approach over an extended length of time and in a manner that is most appropriate while taking into account the talents of different students in a specific classroom.